A study on self-shielding effect of CaCO3 in cable pyrolysis using gas product analysis and PSO optimization - Li, Kaiyuan; Li, Yaoqiang; Jiang, Yaqiang; Zou, Yanyan; Wu, Xujuan; Yang, Yunpeng (Fire safety journal, 2023)
This paper investigates the self-shielding mechanism of CaCO3 during the pyrolysis of PVC-CaCO3 based cable. Previous studies have focused on HCl adsorption by CaCO3, neglecting the self-shielding effect. In this paper, thermogravimetric-infrared analyzer, pyrolysis gas chromatography-mass spectrometer and particle swarm optimization (PSO) algorithm are used to investigate the self-shielding mechanism. The results show a three-stage pyrolysis process. In the first stage, CaCO3 weakens the autocatalytic decomposition of PVC by absorbing HCl in the solid phase. The 3rd Avrami Erofeev model was obtained by PSO, representing the production of CaCl2 crystals. The second stage demonstrates self-shielding due to a reduction in solid-phase porosity. CaCO3 encapsulation inhibits the pyrolysis of PVC resulting in macromolecular intermediates. The 3rd order-based model was obtained by PSO, with a lower pyrolysis reaction rate compared to pure PVC. In the third stage, the stability of Cl in the solid phase is weakened at high temperatures, which converts the Cl to the gas phase in the form of chlorinated hydrocarbons, leading to the failure of self-shielding effect of CaCO3. The 2nd order-based model was obtained by PSO, which is considered as a result of the solid phase reactions instead of pyrolysis. •CaCO3 leads to the self-shielding effect for PVC pyrolysis.•Self-shielding effect of CaCO3 hinders the solid phase degradation of PVC.•Solid Cl can be converted into gas phase owing to self-shielding effect failure.